2018
DOI: 10.1634/theoncologist.2017-0440
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Lenalidomide as Maintenance Therapy After Autologous Stem Cell Transplant in Newly Diagnosed Multiple Myeloma

Abstract: This article provides a summary of the U.S. Food and Drug Administration (FDA) review of the marketing application for lenalidomide as maintenance therapy for patients with newly diagnosed multiple myeloma after autologous hematopoietic stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…Our analyses also demonstrated that, on multivariate analysis, 32 Similar findings were reported from a metaanalysis of consolidation plus lenalidomide maintenance vs lenalidomide maintenance alone, 33 although preliminary findings from the EMN02/HOVON-95 study showed contrasting results, with VRD vs no consolidation, followed by lenalidomide maintenance, resulting in improved PFS in patients aged ≤65 years. 34 Lenalidomide was approved as post-ASCT maintenance therapy in 2017 35 and was not a standard of care at the time of the MMY3012 and MMY3013 studies. Since then it has been shown to offer significant improvements in PFS and OS post-ASCT vs placebo/observation, including PFS benefits in patients aged both <60 and ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses also demonstrated that, on multivariate analysis, 32 Similar findings were reported from a metaanalysis of consolidation plus lenalidomide maintenance vs lenalidomide maintenance alone, 33 although preliminary findings from the EMN02/HOVON-95 study showed contrasting results, with VRD vs no consolidation, followed by lenalidomide maintenance, resulting in improved PFS in patients aged ≤65 years. 34 Lenalidomide was approved as post-ASCT maintenance therapy in 2017 35 and was not a standard of care at the time of the MMY3012 and MMY3013 studies. Since then it has been shown to offer significant improvements in PFS and OS post-ASCT vs placebo/observation, including PFS benefits in patients aged both <60 and ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты большинства проведенных рандомизированных клинических исследований свидетельствовали об улучшении показателей ВБП у больных ММ, получавших после аутоТГСК поддерживающее лечение [13,15,[28][29][30]. Улучшение показателей ОВ определено в опубликованном в 2017 г. P. McCarthy метаанализе, в который было включено 1208 больных ММ, рандомизированных на проведение поддерживающего лечения леналидомидом после аутоТГСК или без посттрансплантационной терапии.…”
Section: Discussionunclassified
“…In February 2017, the Food and Drug Administration in the USA approved the use of lenalidomide as maintenance therapy after autologous HSCT for patients with MM, after showing efficacy and safety in several studies [131]. Lenalidomide has tumoricidal and immunomodulatory activities against MM [132].…”
Section: Consolidation and Maintenance Therapies In MMmentioning
confidence: 99%